Re-contextualizing the standing Sekhmet statues in the Temple of Ptah at Karnak through digital reconstruction and VR experience - Roberta Spallone; Fabrizio Lamberti; Davide Calandra; Davide Mezzino; Johannes Auenmüller; Martina Rinascimento (Disegnare con)
Recent trends in the Digital Humanities – conceived as new modalities of collaborative, transdisciplinary and computational research and presentation – also strongly influence research approaches and presentation practices in museums. Indeed, ongoing projects in museums have considerably expanded digital access to data and information, documentation and visualization of ancient ruins and objects. In addition, 3D modelling and eXtended Reality opened up new avenues of interacting with a wider public through digital reconstructions that allow both objects and sites to be presented through visual narratives based on multidisciplinary scholarly research. The article illustrates the use of 3D digital reconstruction and virtual reality to re-contextualise standing statues of Sekhmet in the Temple of Ptah at Karnak, where they were found in 1818. Today, they are on display at Museo Egizio, Turin. The theoretical framework of the research and the operational workflow – based on the study of the available archaeological, textual, and pictorial data – is presented here. DOI: https://doi.org/10.20365/disegnarecon.31.2023.4